Prediksi Perhitungan Jumlah Produksi Tahu Mahanda dengan Teknik Fuzzy Sugeno - Hajar, Siti; Badawi, Masrof; Setiawan, Yudika Dwi; Siregar, Muhammad Noor Hasan; Windarto, Agus Perdana (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
"Mahanda" tofu industry is a home industry managed by family members located in the city of Pematangsiantar. The purpose of this research is to analyze the amount of "Mahanda" tofu production using fuzzy logic. Sources of data obtained by conducting interviews and direct observation. Fuzzy logic used is the Sugeno method. The variables used are demand variables, inventory variables, and production variables. Each variable has 3 fuzzy sets, the request variable consists of {down, medium, up}. Inventory variables consist of {few, medium, many}. And the production variable consists of {reduced, tolerable and increased}. The test data results there is a difference of error of 0.19% so that this method can be applied to the "Mahanda" tofu factory in the estimated tofu production for the next period.